Lung ultrasound assessment of pulmonary effects of large patent ductus arteriosus in extremely preterm infants beyond the transitional period - Elhanafy, Thanaa; Nasef, Nehad; Ibrahim, Jenna; Awadalla, Rana; Jain, Amish; Mohamed, Adel (The Ultrasound Journal, 2025)
Background: Several studies have suggested a positive association between elevated lung ultrasound scores (LUS) and large patent ductus arteriosus (L-PDA), although findings remain inconsistent. Lung ultrasound score, a semi-quantitative measure of pulmonary aeration loss, has been proposed as a surrogate marker of excessive lung fluid, which may reflect the hemodynamic burden of a significant PDA. The aim of this study was to assess the association between LUS and L-PDA in preterm neonates beyond the initial transitional period and examine its correlations with echocardiographic measures of ductal shunting. This is a cohort retrospective study that included preterm infants born at < 29 weeks’ gestation who underwent LUS within 24 h of targeted neonatal echocardiography. Infants were categorized as having L-PDA (diameter ≥ 1.5 mm, left-to-right shunt) or no/small PDA (< 1.5 mm). Clinical characteristics, LUS, and echocardiographic parameters including PDA diameter, left atrial-to-aortic root (LA: Ao) ratio, and left ventricular output (LVO) were compared. Statistical analyses included univariate, multivariate, and correlation assessments. Results: Among 119 infants included in the analysis, 56 (47%) had L-PDA, and 63 (53%) had no or small PDA. Infants with L-PDA had significantly lower gestational age and higher rates of invasive ventilation. LUS, LA: Ao ratio, and LVO were significantly elevated in the L-PDA group (all p < 0.001). LUS correlated with PDA diameter (r = 0.27, p = 0.003) and respiratory severity score (r = 0.49, p < 0.001). Furthermore, LUS was found to be independently predictive for L-PDA (adjusted OR 1.5; 95% CI: 1.1–1.9). Each 1-point increase in LUS was associated with a 0.14 mm increase in PDA diameter. Inter-rater reliability for LUS was strong (IRR = 0.86). Conclusion: Beyond the transitional period, LUS was significantly associated with PDA size and independently predicted L-PDA in extremely preterm infants.